Automated Guided Vehicle - Ismail, Ahmad Izuan (Universiti Sains Malaysia, 2006)
AGV or “Automated Guided Vehicle” is a system which enables a robot be functional automatically; without any manual control. An AGV robot which is programmed with certain functions is able to carry out tasks by itself without any help from any control or human beings. There are a few modes or methods which are often being used to develop the AGV system. Among them are using camera (webcam), sonar or ultrasonic system and diode emitting sensor. If a camera or webcam is used image processing is the data source for the system. Each image taken will be processed as the robot’s eyesight system. The ultrasonic system uses sound waves to trace any obstacles or objects in its surroundings. The reflections of the waves are used as the data in the AGV system. Diode emitting sensor is the simplest of all AGV tools; for example the line follower. AGV or “Automated Guided Vehicle” is one of the final year projects which develop a robot aided with an eyesight system from a webcam. The AGV robot which had been developed is built on a pair of tyres which is controlled by a DC motor, and 4 wheels which can freely rotate a 3600 rotation without any control from a motor. The two tyres controlled by a DC motor serve the function of controlling the movement of the robot; either left or right movement. There are three important things that must be emphasized during the development of the AGV system using the camera method which is image processing, microcontroller handling and the selection of hardware such as the camera and motor system. The most important system in developing the AGV robot is the image processing from webcam. This process is done using computer technical software called MATLAB7.0 R14. A microcontroller is used to control the motor after receiving signals from the computer. The handling of micro control is vital to determine the smoothness of the AGV robot’s movement. The selection of hardware, such as the type and the capability of the motor, the type of camera, must be done wisely as this hardware is vital elements to produce a reliable AGV robot system.